Cover Image. Issue 12 (13th December 2021) - Li, Shuai; Wang, Tianyu; Hu, Jiqiang; Wang, Bing; Li, Yingze; Wang, Lianchao; Li, Gao; Zhang, Jialin; Zhou, Zhengong
Abstract : The cover image is based on the Original Article Effect of hydroxyapatite content and particle size on the mechanical behaviors and osteogenesis in vitro of polyetheretherketone‐hydroxyapatite composite by Bing Wang et al., https://doi.org/10.1002/pc.26317 .